KEMURIDAN MARIA SEBAGAI INSPIRASI KEMURIDAN GEREJA: TELAAH ATAS TEKS-TEKS PILIHAN TENTANG MARIA DALAM PERJANJIAN BARU - Senda, Siprianus Soleman (Bahasa Indonesia, 2023)
In the scriptures it is clear that Mary was chosen by God to conceive and give birth to Jesus, the Son of God. This special role is both a gift and a task that Mary received in the complete obedience of faith. She listens to the word of God and carries it out with the spirituality of the servant and disciple. Many studies on Mary highlight aspect of motherhood and servant spirituality. Meanwhile, the dimension of Mary's discipleship has received less attention. So this research explores the spirit of Mary’s discipleship in the texts of the scriptures. The aspect of Mary's discipleship is then reviewed for its relevance to today’s followers of Christ (disciples). The bibliography method was used in this research process to find and formulate a synthesis of Mary's discipleship as an inspiration for Church discipleship.The results of the research show that Mary was not only a mother of Jesus and a spiritual mother for Christ’s followers, but also a true disciple, and a role model of discipleship for Church in all ages.